Evidence of Genetic Isolation and Differentiation Among Historically Fragmented British Populations of Common Juniper, Juniperus communis L. - J. Baker; J. Cottrell; R. Ennos; A. Perry; S. A'Hara; S. Green; S. Cavers (Ecology and Evolution)
ABSTRACT Habitat fragmentation and population isolation pose a threat to the genetic diversity and adaptability of many species. The common juniper, Juniperus communis L., a keystone species for juniper scrub habitat and one of only three conifers that are native to the United Kingdom, has been in decline for more than a century in the United Kingdom and across its European range. Remnant UK juniper stands are now often small and highly fragmented, which has raised concerns for their resilience, especially in the face of climate change and the introduction of novel pathogens, such as Phytophthora austrocedri. This work presents a baseline genetic survey of native UK juniper populations and compares patterns of diversity between remnant stands and among three main population centres, or regions, in southern England, the Lake District, and Scotland, using both single nucleotide polymorphism (SNP) and simple sequence repeat (SSR) genetic markers. The aim was to evaluate the standing genetic diversity of native juniper stands, the impacts of habitat fragmentation, and to determine whether juniper populations are genetically isolated from one another. We found that juniper stands, while not completely isolated from one another, face substantial barriers to gene flow, especially between the three population centres. These centres also show different patterns of genetic diversity and population structure, indicating varying levels of internal gene flow. Our findings can provide a baseline from which to monitor the effectiveness of conservation activities, prioritize populations of concern, and guide genetic rescue efforts.